Phylogeography of crossbills, bullfinches, grosbeaks, and rosefinches - Arnaiz Villena, Antonio; Guillén, J.; Ruiz del Valle, V.; Lowy, E.; Zamora, J.; Varela Peña, Pilar; Stefani, D.; Allende Martínez, Luis Miguel (Springer, 2001)
Mitochondrial cytochrome b (cyt b) from 24 Carduelini species including crossbills, bullfinches, grosbeaks, rosefinches, and other related, but not conclusively classified species, was sequenced. These sequences were also compared with all the available sequences from the genera Carduelis, Serinus, and Passer. Phylogenetic analyses consistently gave the same groups of finches and the calculated divergence times suggest that speciation of the studied species occurred between 14 and 3 million years ago (Miocene-Pliocene), appearing before the Passer, Carduelis, and Serinus genera. Pleistocene glaciations may have been important in subspeciation. Crossbills are integrated within the genus Carduelis, and within redpolls; the common crossbill shows subspeciation with Loxia japonica in the Pleistocene epoch. Pinicola enucleator groups together with bullfinches and is probably the ancestor of the group. Hawfinch is only distantly related to the studied groups, and might either represent an isolated genus or be related to the New World genus Hesperiphona. The grosbeak genera Eophona and Mycerobas are clearly sister groups, and species belonging to the former might have given rise to Mycerobas species. The isolated (in classification) Uragus sibiricus and Haematospiza sipahi are included within the genus Carpodacus (rosefinches); Carpodacus nipalensis is outside the genus Carpodacus in the molecular analyses and might be an isolated species or related to the genus Montifringilla. Depto. de Inmunología, Oftalmología y ORL Fac. de Medicina TRUE pub